Functional studies on a novel cytochrome c from Rhodobacter sphaeroides - Li, Bor-Ran (The University of Edinburgh, 2009)
SHP (Sphaeroides Heme Protein) is a monoheme cytochrome c of unknown function. In general, ligands cannot bind to ferric SHP, but some diatomic molecules, such as O2 or NO, can bind to ferrous SHP. The gene encoding SHP and genes encoding a diheme cytochrome c (DHC) and a b-type cytochrome (Cyt-b) are found in the same chromosome region in different species. In the case of Shewanella oneidensis MR-1, mRNA levels for SHP, DHC, and Cyt-b are up-regulated by nearly 10-fold when grown under anaerobic conditions using nitrate as the electron acceptor. Thus it is possible that the physiological role of SHP may be in nitrate metabolism. However, nitrate is too big to be a candidate substrate for SHP, and some nitrification steps need more than one electron transfer (SHP is a monoheme cytochrome). Therefore, we will focus on the nitrite reductase, nitric oxide reductase and nitric oxide dioxygenase activities of SHP. In this thesis it is shown that SHP can catalyse the reaction between oxygen and nitric oxide to give a nitrate ion as the final product. Thus a possible aerobic function for SHP as a nitric oxide dioxygenase is proposed. Aerobically, SHP is proposed to be a nitric oxide dioxygenase which utilizes the same mechanism as other NO dioxygenases, flavohemoglobin (HMP) and neuroglobin (Ngb). This mechanism is proposed to proceed via an oxy-ferrous complex (SHP2+-O2) which reacts with nitric oxide. A mechanism for the catalytic reaction with ferrous-NO complex is described. SHP2+-NO can be quickly converted back to ferrous SHP by reacting with superoxide liberated by SHP2+-O2 or from another source. In addition it is also found that Shewanella MR-1 wild type reveals a higher NO tolerance than the SHP knockout strain in aerobic conditions. The catalytic mechanism of NO dioxygenase is oxygen-dependent, but the SHP mRNA up-regulation in Shewanella oneidensis MR-1 grown with nitrate under anaerobic conditions indicates that SHP may also perform some anaerobic function and may possibly be involved in nitrate metabolism. This work found that SHP reveals anaerobic nitrite reductase activity. However, the catalytic efficiency of SHP is considerably lower than other nitrite reductases. This infers that although SHP can reduce nitrite in vitro, it is unlikely to function as a nitrite reductase in vivo. Ferrous SHP binds NO with a Kd of less than 1 μM, and does not auto-oxidise. Therefore, under anaerobic conditions SHP2+-NO must be processed by some other mechanism. In addition, biochemical results reveal that the SHP/DHC complex has NO reductase activity under anaerobic conditions. Unfortunately, this function was not proved in vivo. SHP was initially isolated from Rhodobacter sphaeroides and its structure was reported in 2000. Based upon this structure, SHP is clearly a class I cytochrome c with one axial histidine ligand to the heme iron. Unusually, however, it has an asparagine residue as the other axial heme ligand, and as such is unique among cytochromes c. For this reason it may be assumed that the asparagine plays a special role. This study reveals several potential reasons why SHP utilises asparagine as a heme ligand. Firstly, in the ferric form, asparagine 88 binds to the heme iron to prevent small molecules binding. Secondly, in the ferrous form it moves to allow oxygen to bind and form the oxy-ferrous complex, using hydrogen bonding for stability. Thirdly, using asparagine as a heme ligand creates a suitable redox potential for reduction by DHC, thus allowing NO dioxygenation.
Keywords: crystal structure; c-type cytochrome; nitric oxide dioxygenase; Rhodobacter